Can student health professionals accurately estimate alcohol content in commonly occurring drinks?. (August 2016) - Sinclair, Julia; Searle, Emma
Objectives: Correct identification of alcohol as a contributor to, or comorbidity of, many psychiatric diseases requires health professionals to be competent and confident to take an accurate alcohol history. Being able to estimate (or calculate) the alcohol content in commonly consumed drinks is a prerequisite for quantifying levels of alcohol consumption. The aim of this study was to assess this ability in medical and nursing students. Methods: A cross-sectional survey of 891 medical and nursing students across different years of training was conducted. Students were asked the alcohol content of 10 different alcoholic drinks by seeing a slide of the drink (with picture, volume and percentage of alcohol by volume) for 30 s. Results: Overall, the mean number of correctly estimated drinks (out of the 10 tested) was 2.4, increasing to just over 3 if a 10% margin of error was used. Wine and premium strength beers were underestimated by over 50% of students. Those who drank alcohol themselves, or who were further on in their clinical training, did better on the task, but overall the levels remained low. Conclusions: Knowledge of, or the ability to work out, the alcohol content of commonly consumed drinks is poor, and further research is needed to understand the reasons for this and the impact this may have on the likelihood to undertake screening or initiate treatment.